Effect of child-centered play therapy on anxiety and stress symptoms among pre-school children in Pusat Anak Permata Negara, Malaysia - Lim, Yanjun (2015)
Every human being including children experience anxiety and stress. A certain amount of anxiety and stress is beneficial, especially for children to develop skills in coping with challenging situations across their life span. However, when the anxiety and stress level become overwhelming and untreated, it will lead to lifelong physical and mental health problems. Hence, an early intervention is crucial as prevention is always better than cure. This study aimed to examine the effect of Child-centered Play Therapy (CCPT) on young children with anxiety and stress symptoms. This study was conducted in 10 Pusat Anak PERMATA Negara (PAPN) in Malaysia which included the state of Negeri Sembilan, Perak, Pahang, Federal Territories,Selangor and Malacca. Quasi-experimental design was used in this study with quantitative methods adopted. There were three stages in current study that is the pretest stage (first stage), the intervention stage (second stage) and the post-test stage (third stage). In the first stage, pre-test was carried out on 299 PAPN children to assess whether they have anxiety and stress symptoms. Caregiver-Teacher Report Form (CTRF) was used to screen and assess children‟s anxiety and stress levels. Results showed that 67 of them were found to have anxiety and stress symptoms. They were then included to the second stage and divided into experimental group (with play therapy) and control group (without play therapy). Play therapy sessions were carried out for two to three months on respondents in the experimental group, depending on the children‟s progress as determined by the play therapists. Post-test was carried out on in both groups after 3 months, after completion of stage two. The results indicated that there were significant decrease with large effect size in both anxiety and stress scores between pre- and post-experimental group as compared to control group. For the differences among male and female children, both genders in experimental group reported significant decrease in anxiety and stress scores with large effect size too. In conclusion, the findings of current study demonstrated that Child-centered Play Therapy was effective in decreasing the anxiety and stress level among children studied regardless of their genders. This study has further supported that play therapy is a developmentally appropriate intervention in treating young children with anxiety and stress symptoms. Practical programs such as training or workshops should be organized by related agencies for teachers or parents to know about the mental health condition of young children, the importance of play and play therapy.